Preparation and characterization of high yield cellulose nanocrystals (CNC) derived from ball mill pretreatment and maleic acid hydrolysis. (15th April 2020) - Seta, Frederikus Tunjung; An, Xingye; Liu, Liqin; Zhang, Hao; Yang, Jian; Zhang, Wei; Nie, Shuangxi; Yao, Shuangquan; Cao, Haibing; Xu, Qingliang; Bu, Yifan; Liu, Hongbin
Graphical abstract: A facile and green approach to prepare cellulose nanocrystals (CNC) with high yield and colloidal stability from bamboo fibers by maleic acid hydrolysis is presented. The aim to pretreat bamboo fibers with ball mill before maleic acid hydrolysis is to destroy and open up the solid structure of bamboo fibers, to facilitate the following accessibility of maleic acid molecules into bamboo fiber structure, and to help expose more free hydroxyl groups from C2, C3, and C6 of cellulose chains that can be esterified by maleic acid molecules to form cellulose maleate. Ball mill pretreatment would guarantee more maleic acid molecules into the destroyed bamboo fiber structure and induce sufficient hydrolysis of amorphous regions of fibers, thus releasing more satisfactory CNC particles, i.e., a higher CNC yield; in addition, more maleic acid molecules would be esterified with hydroxyl groups during hydrolysis to impart rich carboxyl groups to CNC, i.e., a higher colloidal stability, compared with the control CNC sample without ball mill pretreatment. Highlights: Ball mill process can open up the firm structure of bamboo fibers. Ball mill-treated bamboo fibers would expose more accessible hydroxyl groups. More acid molecules can be penetrated into the structure of destroyed fibers. Maleic anhydride can be more easily reacted with −OH to generate −COOH. The method induces a higher CNC yield and colloidal stability than the control. Abstract: The target of the study is to improve the yield and the colloidal stability of cellulose nano-crystals (CNC) that is obtained through maleic acid hydrolysis. Herein, a facile/ green approach to prepare CNC with high yield and colloidal stability from bamboo fibers is presented. Ball mill pretreatment can break down and open up the structure of bamboo fibers, thus exposing more hydroxyl groups on the surface of pulp fibers and increasing the access of acid molecules into pulp fibers. The maleic acid molecules can easily hydrolyze cellulose, thus releasing more crystalline parts; maleic acid anhydride can react with hydroxyl groups to generate more −COOH groups on CNC. The yield of resultant CNC was 10.55–24.50 %, which was much higher than 2.80 % of the control. The study put forward a facile approach to prepare CNC with high yield and colloidal stability, and paves a possible way for industrialization of CNC production.